Review of the Cretaceous avian diversity of Antarctica: a changing scenario for the evolution of early Neornithine birds - Acosta Hospitaleche, Carolina Ileana Alicia; Irazoqui, Facundo Martín; Bona, Paula; Paulina Carabajal, Ariana
The worldwide record of Cretaceous Neornithes and Neornithine-like birds is both controversial and poorly understood. However, in recent years, the Antarctic continent has yielded a substantial number of Maastrichtian avian specimens, contributing significantly to our understanding of the early evolution of this group. Simultaneously, the keen interest and collaborative efforts of various paleornithologists have resulted in a wealth of knowledge, which we have thoroughly reviewed, updated, and discussed in the context of recent discoveries. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Irazoqui, Facundo Martín. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Bona, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Paulina Carabajal, Ariana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina